2017
DOI: 10.1136/jclinpath-2017-204525
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 protein expression in tumour cells and immune cells in mismatch repair protein-deficient and -proficient colorectal cancer: the foundation study using the SP142 antibody and whole section immunohistochemistry

Abstract: AimsRoutine application of PD-L1 immunohistochemistry (IHC) in colorectal cancer (CRC) is limited due to lack of standardized scoring criteria, antibody clones, and intratumoral staining heterogeneity. We assessed PD-L1 protein expression on full face CRC tissue sections and applied two algorithms based on the published clinical trials that support the recent FDA approval for immune checkpoint inhibitors (ICPI) therapy in non-small cell lung cancer (NSCLC). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
2
14
1
Order By: Relevance
“…In a study on lung adenocarcinoma, a correlation between high histological differentiation and PD-L1 expression on TCs and IECs was found [17]. Jabbour et al found a correlation between PD-L1 expression on TCs and IECs and tumor advancement [18]. However, other studies did not confirm these findings [19] in line with our own results.…”
Section: Discussioncontrasting
confidence: 48%
“…In a study on lung adenocarcinoma, a correlation between high histological differentiation and PD-L1 expression on TCs and IECs was found [17]. Jabbour et al found a correlation between PD-L1 expression on TCs and IECs and tumor advancement [18]. However, other studies did not confirm these findings [19] in line with our own results.…”
Section: Discussioncontrasting
confidence: 48%
“…We used the latter value for the objective difficulties in the detection of very rare positive neoplastic cells and to avoid overestimating of PD-L1 expression. In addition, like few other studies [ 39 41 ], we evaluated PD-L1 not only in neoplastic cells but also in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients would benefit from PD‐1/L1, even if their PD‐L1 are negatively expressed. Predictive markers for PD‐1/L1 inhibitors are not just limited to PD‐L1 expression such as microsatellite instability, tumor mutation burden, DNA mismatch repair, T cell receptors sequencing and so forth. Except for that, many genes or mRNA base model also claimed for its predictive value in immune therapeutic efficacy, but up to now, how to accurately select patients that would benefit from immune therapy remains a complex project.…”
Section: Discussionmentioning
confidence: 99%